PERSEPSI MAHASISWA JURUSAN PENDIDIKAN IPS FKIP UNS TERHADAP PENGGUNAAN E-LEARNING SEBAGAI UPAYA PENINGKATAN KUALITAS PEMBELAJARAN - Setyowibowo, Feri (MIIPS, 2010)
E-learning has become one of education trends that can increase the learning quality. But to be able to get its benefit, students and lecturers attitudes should show proper attitude toward the e-learning.This research aims to know the description of Social Sciences Education Depatment students of Teachers Training and Education Faculty of Sebelas Maret University perceptions toward the use of e-learning to increase the learning quality and to probe the future development should be made to increase its acceptance. Using descriptive quatitative analysis toward 129 students, the research shows that the learning activities were still not optimum, showed by only few subjects that had already implemented the e-learning. The research also showed that students perceived that the infrastructures and facilities had suitable enough. In boosting the use of e-learning in the future, students perceived that the proper trainings and simplicity to use the e-learning will attract the future use of this elearning.